The implication of innovation system approach in Malaysian agricultural biotechnology development: Accomplishments and propositions - Farid, Hadi; Silong, Abu Daud; Hamzah, Azimi (Centre for Extension, Entrepreneurship and Professional Advancement (APEEC), Universiti Putra Malaysia, 2010)
The need to increase agricultural production in the long-term is an imperative given the pace of global population growth rate. The development of new technologies to increase crop yields becomes a prerequisite. Biotechnological innovations are envisaged to play a major role in meeting this challenge. This paper explores the level of innovation actions in agricultural biotechnology in Malaysian agro-biotechnology companies. The innovative representation of agricultural biotechnology is dependent upon research, education, extension, and farmers as the main actors. These actors should be given the opportunity to collaborate and enrich each other with information and feedback to facilitate the flow of technology transfer. It is observed that the linkage among the actors is weak in Malaysia and has to be strengthened. The government can encourage and reinforce the interaction and linkage among the actors, namely between developers/researchers and the users through legislations and flexible administrative policies. In Malaysia, the number of the biotechnology companies and the quality of the existing firms‟ activities is satisfactory; however, there is still a long way to go to achieve the goals set by the Ninth Malaysian Plan. This paper analyses the factors affecting innovation activities in Malaysia and provides suggestions to improve the situation.